(untitled) (Northern International Medical College Journal, 2018)
Background : Infantile colic is one of the common pediatric problems that Pediatricians encounter in practice. This condition is associated with excessive crying in healthy thriving infants over a regular period during the day and is sustained for the first few months of life. It has been historically described as irritable or compulsive crying or paroxysmal fussing with multifactorial etiology. Although it affects 5-19% of young infants, it remains a frustrating problem for parents and caregivers, because it is difficult to treat and may result in significant psychosocial consequences. Different treatment options are available with no definitive and conclusive benefit. In this metaanalysis, we pooled relevant data regarding the use of probiotics in infantile colic and tried to find out any beneficial effect thereof. Objective : To evaluate the efficacy of probiotics supplementation in the reduction of the duration of crying time in infantile colic. Method : It is a comprehensive meta-analytic study where literature searches were conducted in the Pubmed using end note package and Google scholar. Randomized controlled trials those enrolled healthy, term breastfed infants with infantile colic were included for analysis. After meticulous scrutiny for methods and study population, five studies with a total of 384 breastfed infants were selected for final analysis. All these studies used Lactobacillus reuteri DSM 17938 as probiotics in the therapeutic intervention and supplementation of this was compared to placebo. Result : Analysis of pooled data showed that at Initiation of therapy mean difference of crying time 0.29 minutes; 95% CI-6.61, 7.20, p=0.89, after 3weeks of probiotics therapy mean difference of crying time -30.64, 95% CI- 34.48, -26.81, p=0.0001. Conclusions : Probiotics use for 3 weeks significantly reduced the duration of crying time in exclusively breastfed infants suffering from infantile colic. Northern International Medical College Journal Vol.9(1) July 2017: 245-247